2021
DOI: 10.1093/cz/zoab019
|View full text |Cite
|
Sign up to set email alerts
|

Queens remate despite traumatic mating in stingless bees

Abstract: Males can control female reproduction using genital plugs to impede access by rivals. In social bees, ants and wasps, plugging may involve traumatic mating, with females being harmed. In stingless bees, chances are that plugs may promote ovarian activation, and are thought to ensure single mating—a general tendency among the social Hymenoptera. However, understanding on relationships between mating plugs, traumatic mating, and mating systems in stingless bees remains limited. To address this, we (i) compared m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…In principle, such proximity among related colonies might promote inbreeding, and studies have shown that the gynes of some stingless bee species such as Melipona mondury, M. beecheii, Lestrimellitta limao, Nannotrigona perilampoides, Paratrigona subnuda, S. postica, and S. depilis can mate up to six times (Paxton et al, 1999a;Paxton, 2000) but others, such as Trigona fulviventris, just once (Green & Oldroyd, 2002;Palmer et al, 2002;Vollet-Neto et al, 2018;Vollet-Neto et al, 2019). Veiga et al (2021) suggested that the quality of the plug formed by the male genitalia remaining in the mated queen is involved because such plugs that are difficult for the queen to remove and thereby increase the probability of single mating. There is also a trade off between single and multiple mating strategies.…”
Section: Polyandry and Gene Flow In A Stingless Beementioning
confidence: 99%
See 1 more Smart Citation
“…In principle, such proximity among related colonies might promote inbreeding, and studies have shown that the gynes of some stingless bee species such as Melipona mondury, M. beecheii, Lestrimellitta limao, Nannotrigona perilampoides, Paratrigona subnuda, S. postica, and S. depilis can mate up to six times (Paxton et al, 1999a;Paxton, 2000) but others, such as Trigona fulviventris, just once (Green & Oldroyd, 2002;Palmer et al, 2002;Vollet-Neto et al, 2018;Vollet-Neto et al, 2019). Veiga et al (2021) suggested that the quality of the plug formed by the male genitalia remaining in the mated queen is involved because such plugs that are difficult for the queen to remove and thereby increase the probability of single mating. There is also a trade off between single and multiple mating strategies.…”
Section: Polyandry and Gene Flow In A Stingless Beementioning
confidence: 99%
“…In contrast, polyandry (multiple mating) decreases the frequency of diploid males, reduces parasitism, and increases genetic diversity (Baer & Schmid-Hempel, 1999;Tarpy & Page Jr, 2001;Borges et al, 2010;Jaffé, 2014). Thus, whether colonies have single or multiple patrilines depend upon the species, the efficacy of mating plugs and other factors still to be revealed (Peters et al, 1999;Veiga et al, 2021). In prior studies with S. mexicana, Kraus et al (2008) found that the majority of patrilines in managed colonies apparently originated from wild colonies and not from managed ones within the same meliponaries.…”
Section: Polyandry and Gene Flow In A Stingless Beementioning
confidence: 99%
“…Previous studies on the reproduction of bumblebee queens have focused on ovarian status, hormone effects, nutritional metabolism, feed composition, intestinal bacteria species, and environmental factors [6][7][8][9][10][11]. Most insects reproduce sexually, and the physiology and behavior of female insects change post mating [12][13][14][15][16][17]. After honey bee and bumblebee queens mate with drones, the expressions of immune-and sperm storage-related genes in spermathecae are significantly up-regulated [18,19].…”
Section: Introductionmentioning
confidence: 99%